IMPROVING EDUCATION QUALITY MANAGEMENT IN PRIVATE HIGHER EDUCATION INSTITUTIONS (Marketing Journal, 2025)
This article examines the issues of improving the management of education quality in private higher education institutions. Using the example of the University of Business and Science (UBS) in Namangan, a SWOT analysis was conducted to assess the strengths, weaknesses, opportunities, and threats in ensuring educational quality. International approaches — TQM, EFQM Excellence Model, and ISO 21001:2018 — were analyzed, highlighting their appli cability to the national context. In addition, based on presidentia l decrees, as well as the research of foreign and local scholars, methodological foundations for quality management in education were developed. The 305 study provides practical recommendations for introducing innovative mechanisms to enhance education quality in private universities.
Keywords: Private higher education; quality of education; management system; UBS University; SWOT analysis; inte rnational standards; TQM; EFQM